Key Factors Influencing Work Environment, Motivation, and Engagement in Promoting Organizational Citizenship Behaviour - Ishak, Ishak (Journal of Economic Education and Entrepreneurship Studies, 2024)
Every organization, both private and government, will strive to encourage organizational citizenship behavior in its employees in order to achieve its vision and mission. The purpose of this research is to determine the influence of the work environment, work motivation, and work involvement on organizational citizenship behavior in employees of the Pontianak City Environmental Service. This type of research is quantitative. Data collection was carried out by distributing questionnaires to 40 employees who were the research samples, using saturated sampling techniques. The data analysis technique uses multiple linear regression analysis with the Statistical Package for the Social (SPSS) version 26 analysis tool. The results of this study show that H1 is rejected, meaning that the work environment partially has no effect on employee organizational citizenship behavior. Then H2 was rejected, which means that work motivation has no effect on employee organizational citizenship behavior, while H3 was accepted, which means that work involvement has a positive and significant effect on employee organizational citizenship behavior. The drawback of the research is that the scope is too narrow. This research only focuses on administrative employees of the Pontianak City Environmental Service, which may limit the conclusions of the findings to all employees or other organizations with different characteristics. The research suggestion is to expand the sample and research locations so that the research findings can be more conclusive.